To solve the equation, -4(x - 8) = -32, you can start by distributing -4 to the terms inside the parentheses:
-4(x - 8) = -4*x + (-4)*(-8) = -4x + 32
Now, the equation becomes -4x + 32 = -32.
Next, you can isolate the variable by subtracting 32 from both sides of the equation:
-4x + 32 - 32 = -32 - 32
This simplifies to -4x = -64.
To solve for x, divide both sides of the equation by -4:
(-4x)/(-4) = (-64)/(-4)
Simplifying further:
x = 16
Therefore, the solution to the equation is x = 16.
What is the solution of the equation -4(x - 8) = -32 when solving for x?
1 answer